2018
DOI: 10.1021/acssuschemeng.8b04717
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Study of Thermal and (Bio)Degradable Properties of Semiaromatic Copolyesters Based on Naturally Occurring Isosorbide

Abstract: Here we present a series of copolyesters of poly­(butylene terephthalate) (PBT) with the renewable building block isosorbide (1,4:3,6-dianhydro-d-glucitol, IS), designated PBIT. The aim of this work is to systematically elucidate how the inherent properties (reactivity, structural asymmetry, structural rigidity, and hydrophilicity) of IS would affect the synthesis and thermal/(bio)­degradable performance of PBIT copolyesters. The target copolyesters containing 0–50 mol % IS units were successfully synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 44 publications
4
50
0
Order By: Relevance
“…This indicates that the incorporation of LA units made the thermal‐mechanical properties of the PETLAs fibers exhibited better flexibility. [ 40,41 ] The glass transition behavior of PETLAs fibers amorphous phase decreased with the increase of LA units, and the Tg decreased from 65 to 60 °C. The correlation between T g and LA content was basically consistent with DSC analysis results in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the incorporation of LA units made the thermal‐mechanical properties of the PETLAs fibers exhibited better flexibility. [ 40,41 ] The glass transition behavior of PETLAs fibers amorphous phase decreased with the increase of LA units, and the Tg decreased from 65 to 60 °C. The correlation between T g and LA content was basically consistent with DSC analysis results in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…35 Our previous study regarding the (bio)degradability of terephthalic acid-based copolyesters showed that the presence of IS moieties enhances the hydrolytic degradation of the polymers to a certain extent, yet insignificantly influences their biodegradation properties. 23 For PBIF copolyesters, the crystallinities are much inhibited which, together with the high hydrophilicity of the materials, might result in degradable polyesters with enhanced thermal properties. To evaluate the degradation performance of the synthesized copolyesters, film samples of PBF homopolyester and PBIF copolyesters containing 7, 17, 27 and 51 mol% of IS were prepared and investigated under neutral hydrolytic, acidic hydrolytic and enzymatic degradation environments.…”
Section: Degradability Of Copolyestersmentioning
confidence: 99%
“…PP enzyme comes from animal pancreas after crystallization and has been frequently employed for biodegradation assay of polyesters. 23,36,37 Recently, a number of studies have shown that cutinase exhibits high efficiency for depolymerizing aliphatic or aromatic polyesters, [38][39][40] which significantly reduces the observation duration of enzymatic degradation experiments. The mechanism of both enzymes for degrading polyesters is generally believed to be via ester bond scission by a nucleophilic substitution process.…”
Section: Enzymatic Degradationmentioning
confidence: 99%
See 2 more Smart Citations